Singularly perturbed linear boundary-value problems with pulse effects and the regular reduced problem - Karadzhov, Yu. A. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
A singularly perturbed linear boundary-value problem with pulse effect is considered. By using pseudo-inverse matrices, we construct an asymptotic solution with a single boundary layer.